2017
DOI: 10.1038/leu.2017.63
|View full text |Cite
|
Sign up to set email alerts
|

Treatment-free remission following frontline nilotinib in patients with chronic myeloid leukemia in chronic phase: results from the ENESTfreedom study

Abstract: The single-arm, phase 2 ENESTfreedom trial assessed the potential for treatment-free remission (TFR; i.e., the ability to maintain a molecular response after stopping therapy) following frontline nilotinib treatment. Patients with Philadelphia chromosome-positive chronic myeloid leukemia in chronic phase with MR4.5 (BCR-ABL1⩽0.0032% on the International Scale (BCR-ABL1IS)) and ⩾2 years of frontline nilotinib therapy were enrolled. Patients with sustained deep molecular response during the 1-year nilotinib cons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
231
0
16

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 254 publications
(258 citation statements)
references
References 28 publications
11
231
0
16
Order By: Relevance
“…In recent clinical practice it has been shown that, after an adequate period of treatment and in the presence of a very deep and stable molecular response, TKI treatment can be safely discontinued, with good chance of success [7,19]. Numerous studies showed the efficacy of nilotinib in the first-line treatment of Philadelphia chromosome-positive chronic myeloid leukemia adult patients [6,19,20].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In recent clinical practice it has been shown that, after an adequate period of treatment and in the presence of a very deep and stable molecular response, TKI treatment can be safely discontinued, with good chance of success [7,19]. Numerous studies showed the efficacy of nilotinib in the first-line treatment of Philadelphia chromosome-positive chronic myeloid leukemia adult patients [6,19,20].…”
Section: Discussionmentioning
confidence: 99%
“…In the following years, second-generation TKIs -dasatinib and nilotinib -were introduced, all showing the ability to induce molecular and cytogenetic responses in patients who had failed therapy with imatinib. Over the years, several trials demonstrated the superiority of nilotinib and dasatinib vs imatinib in the first-line treatment; these two drugs were associated to a higher rate of major molecular response (MMR) and deep molecular responses (MR 4.0 and MR 4.5 ), and to a lower percentage of progression of the chronic phase to the most advanced disease stages [6][7][8].…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Even though 2nd generation TKIs are more potent in terms of deep molecular remission (DMR) compared to imatinib [2][3][4] CP-CML patients qualify for a TKI discontinuation attempt [5]. Novel combination therapies of available TKIs together with novel drugs, such as ABL001 in patients with a lower likelihood to achieve continuous DMR should be tested [6].…”
mentioning
confidence: 99%